2001
DOI: 10.1002/jlcr.25804401171
|View full text |Cite
|
Sign up to set email alerts
|

Kit formulation and preliminary toxicity of [99mTc(CO)3]+ intermediate: A novel technetium radiopharmaceutical platform

Abstract: The radiochemistry of 99"'Tc carbonyl complexes has been expanding over the last few years following the basic chemistry advances of preparing the [Tc(CO)3]' core in aqueous solution directly from perte~hnetatel-~. The field is participating in research of novel organometallic molecules for specific brain imaging receptors, in addition to finding wide applications in protein and peptide labeling4.'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Preliminary investigations using HPLC have confirmed the formation of Tc carbonyl core while using the freeze dried kit. 24 It has shown that the formulation is reproducible, robust and simple for the preparation of 99m Tc(OH 2 ) 3 (CO) 3 precursor. Complexation studies of histidine with kit precursor have been carried out earlier to confirm its utility for synthesis of tricarbonyl complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary investigations using HPLC have confirmed the formation of Tc carbonyl core while using the freeze dried kit. 24 It has shown that the formulation is reproducible, robust and simple for the preparation of 99m Tc(OH 2 ) 3 (CO) 3 precursor. Complexation studies of histidine with kit precursor have been carried out earlier to confirm its utility for synthesis of tricarbonyl complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these complexes can be formed with very small amounts of the ligand, resulting in preparations with extremely high specific activity. Recently, the preparation of the intermediary tri-aqua tricarbonyl Tc(I) core has been further optimized by using potassium boranocarbonate (K 2 BH 3 CO 2 ) as both a solid source of CO and the reductant for labeling with 99m Tc (Dyszlewski et al 2001). This has allowed the production of a kit formulation for the preparation of the tricarbonyl Tc(I) intermediate, which can then be further used for convenient production of a wide diversity of Tc(I) tricarbonyl compounds by ligand for water exchange.…”
Section: Tc(i) Tricarbonyl Complexesmentioning
confidence: 99%
“…Over the last years, the radiochemistry of 99m Tc‐tricarbonyl complexes has been extended to find useful applications in radiochemistry and nuclear medicine. The basis for this kind of radiochemistry is the convenient preparation of the Tc‐tricarbonyl precursor [ 99m Tc(CO) 3 (H 2 O) 3 ] + either in the classic way with CO gas and borohydride reduction or with an IsoLink kit . In the resulting precursor, the three water molecules can easily be replaced by ligands that contain suitable donor atoms to form stable complexes.…”
Section: Introductionmentioning
confidence: 99%